2023
DOI: 10.3390/v15071450
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Diversity and Evolution of SARS-CoV-2 Lineages in Pakistan

Abstract: The emergence of SARS-CoV-2 variants has posed a challenge to disease control efforts worldwide. This study explored the genomic diversity and phylogenetic relationship of SARS-CoV-2 variants reported in Pakistan. Our objective was to understand the transmission dynamics of different lineages within the country. We retrieved and analyzed spike protein sequences from Pakistan and compared them with reference sequences reported worldwide. Our analysis revealed the clustering of Pakistan-origin isolates in nine d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Previous studies have mainly reported that VOCs have more genetic mutations (such as T4685A, N4992N, and G5063S in RNA-dependent RNA polymerase [RdRp]; T19R and T19I in the spike N-terminal domain; and N440K, K444N, Q493R and N532H in the spike receptor-binding domain), ( Saifi et al, 2022 ) possibly contributing to increased transmission, virulence, mortality, and immune escape ( Carabelli et al, 2023 ; Aziz et al, 2023 ; Davies et al, 2021 ). Although NCT is known to be closely related to clinical manifestations in SARS-CoV-2 cases ( Yang et al, 2021 ; Zang et al, 2022 ; Wang et al, 2022 ; Atluri et al, 2022 ), there is a lack of evidence on the effects of mutations in different SARS-CoV-2 strains on NCT.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have mainly reported that VOCs have more genetic mutations (such as T4685A, N4992N, and G5063S in RNA-dependent RNA polymerase [RdRp]; T19R and T19I in the spike N-terminal domain; and N440K, K444N, Q493R and N532H in the spike receptor-binding domain), ( Saifi et al, 2022 ) possibly contributing to increased transmission, virulence, mortality, and immune escape ( Carabelli et al, 2023 ; Aziz et al, 2023 ; Davies et al, 2021 ). Although NCT is known to be closely related to clinical manifestations in SARS-CoV-2 cases ( Yang et al, 2021 ; Zang et al, 2022 ; Wang et al, 2022 ; Atluri et al, 2022 ), there is a lack of evidence on the effects of mutations in different SARS-CoV-2 strains on NCT.…”
Section: Introductionmentioning
confidence: 99%